Diversity and life-history traits of wild bees (Insecta: Hymenoptera) in intensive agricultural landscapes in the Rolling Pampa, Argentina. Issue 19 (26th May 2016) - Le Féon, Violette; Poggio, Santiago L.; Torretta, Juan Pablo; Bertrand, Colette; Molina, Gonzalo A. R.; Burel, Françoise; Baudry, Jacques; Ghersa, Claudio M.
ABSTRACT: The decline of bees is a major concern due to their vital role in pollinating many crops and wild plants. Some regions in South America, and especially the Pampas, are amongst those parts of the world where stressors of bee populations have been little studied. The Pampas has been intensively transformed for agriculture, being presently one of the most productive areas of agricultural commodities in the world. Here, we aim to provide first insights on the taxonomic and functional composition of bee assemblages in the Rolling Pampa, the most intensively managed part of the Pampas. Soybean (herbicide-tolerant genetically modified varieties) is the predominant crop in this region. Bees were sampled with coloured pan traps. Sampling points were located on field margins in either the cropped or the semi-natural grassland area of a farmland site devoted to annual cropping. A total of 2384 individuals were caught, representing 33 taxa [mainly (morpho)species]. The subgenus Lasioglossum ( Dialictus ) largely dominated captures (78% of the total abundance) and was relatively abundant in the entire study area, suggesting that some species are likely to reach their ecological requirements in cropped areas. No-till fields and field margins may provide large areas for these below-ground nesting species, while their polylectic food preferences allow them to collect pollen on a wide range of plant species, among them possibly soybean. On the contrary, the richness and the abundance of other taxa were higher in the semi-natural area than in the cropped area. Among them, above-ground nesting or oil-collecting species, which have more specialised nesting and floral requirements, were highly associated with the semi-natural area. Our findings highlight the large dominance of L . ( Dialictus ) species in this highly intensively managed landscape, and the urgent need of preserving semi-natural habitats to maintain species-rich and functionally diverse bee communities in the Pampas.